Wahlenbergfjord, eastern Svalbard: a glacier‐surrounded fjord reflecting regional hydrographic variability during the Holocene?. (5th June 2018) - Bartels, Martin; Titschack, Jürgen; Fahl, Kirsten; Stein, Rüdiger; Hebbeln, Dierk
Abstract : Exceptionally high sedimentation rates in Arctic fjords provide the possibility to reconstruct environmental conditions in high temporal resolution during the (pre‐)Holocene. The unique geographical location of Svalbard at the intersection of Arctic and Atlantic waters offers the opportunity to estimate local (mainly glacier‐related) vs. regional (hydrographic) variabilities. Sedimentological, micropalaeontological and geochemical data from the very remote, glacier‐surrounded Wahlenbergfjord in eastern Svalbard provides information on glacier dynamics, palaeoceanographic and sea‐ice conditions during the Holocene. The present study illustrates a high meltwater discharge during the summer insolation maximum ( c. 11.3–7.7 ka) when the intrusion of upwelled relatively warm Atlantic‐derived waters led to an almost open fjord situation with reduced sea ice in summer. Around 7.7 ka, a rapid hydrographic shift occurred: the dominance of inflowing Atlantic‐derived waters was replaced by a stronger influence of Arctic Water reflecting regional palaeoceanographic conditions evident in the benthic foraminiferal fauna also at Svalbard's margins. Neoglacial conditions characterized the late Holocene ( c. 3.1–0.2 ka), when glaciers probably advanced as cold atmospheric temperatures were decoupled from the advection of relatively warm intermediate waters probably caused by an extending sea‐ice coverage. Accordingly, our data show that even a remote, glacier‐proximal study site reflects rapid as well as longer‐term regional changes.